BUSI 4555 Management Project (Business analysis project: company-based project / business plan analysis) Growth strategy for Hexa, a Malaysian SME company - Pan, Choon Seong (2023)
Faced with a slowing rate of growth and the ongoing Covid-19 pandemic, an SME-sized local food manufacturing company like Hexa Food is facing challenges to identify new growth opportunities in the business environment, choose the right growth strategies and build its competitive advantage and organisation structure to achieve a long-term sustainable business. Hence, this research aspires to explore the various types of growth strategies from literature and analyse the internal and environment factors that affect the choice of growth strategies. The analysis from this research is intended to assist an SME company like Hexa to embark on a diversification strategy to enter a new market with new products and services, in this case the tech services sector. A conceptual framework of growth was developed to summarise the proposed steps for implementation.